Сучасні підходи до тлумачення мотиву номінації - Chornous, Oksana; Чорноус, Оксана (My University, 2018)
This paper is focused on some modern approaches to the interpretation of the term “motive for naming”, which is widely used in Ukrainian onomastics. In author’s opinion, it is necessary to define the semantic content of the terms “motive” and “naming” by analyzing the definitions given by the linguists and psychologists in different lexicographical works and papers. As a result of the investigation, it appeared that there are some essential components of the terms “motive” and “naming”: 1) it is an internal reason for a certain course of action; it is conscious; 2) this reason holds great personal significance for a namegiver, it is self-interest for a namegiver; 3) it is an internal reason that energizes people to use all resources of language and makes him/her to choose between ready lexical units that function in a language and can be used for naming or create new names; 4) in the process of creating an anthroponym, the speaker is guided by his/her tastes and preferences, trying to achieve the maximum informative value for the name and so on. Compared to components given in the definition of the term “motive for naming”, the author notes some differences. For example, some scholars defined motive of naming as an external extra-linguistic reason. On the basis of the current legislation it was also determined that the term “motive for naming” can be applied to surnames, especially in the cases when the surname was created by the representatives of local authorities or the person by himself. У статті досліджуються сучасні підходи до тлумачення терміну «мотив номінації», який останнім часом активно вживається в українській ономастиці. Автор з’ясовує семантичне наповнення понять «мотив» і «номінація», аналізуючи дефініції, запропоновані лінгвістами та психологами в лексикографічних працях, наукових розвідках. У результаті були виявлені такі істотні ознаки понять «мотив» і «номінація»: 1) ідеться про внутрішню усвідомлювану мовцем причину; 2) ця причина має особисту значущість для номінатора, є сферою його індивідуального зацікавлення; 3) внутрішня причина спонукає номінатора звернутися до ресурсів мови та обрати з-поміж готових лексем, що функціо-нують у мові, найбільш вдалий варіант або створити власний; 4) створюючи антропонім, мовець керується своїми смаками та вподобаннями, намагаючись досягти максимальної інформативності, милозвучності оніма. Порівнюючи їх із закладеними в дефініцію терміна «мотив номінації», автор робить висновок про деякі розбіжності, зокрема в деяких визначеннях мотив номінації інтерпретують як зовнішню екстралінгвістичну причину. Насамкінець на підставі чинного законодавства автор робить висновок про те, що термін «мотив номінації» може бути застосований до прізвищ як класу онімної лексики, зокрема в тих випадках, де творцем прізвища виступають представники державних органів або сам носій.
Modern Approaches to the Interpretation of the Motive for Naming.
Keywords: мотив; номінація; ономастика; психологія; прізвище; motive; naming.; onomastics; psychology; surname